Thesis Writing at Master’s Level in Education - Avasthi, Tara Prasad (The Third Pole: Journal of Geography Education, 2014)
This paper has highlighted the thesis writing format for Master’s Degree in Education at Tribhuvan University, Kathmandu. It briefly describes the process to make uniformity in the style of writing. Here focus has been given on American Psychological Association (APA) style. This format is commonly adopted in most of the Departments in the Tribhuvan University, and Department of Geography Education is one of them. It is essential for the students and researchers who involve in theses research and formatting their writings. It is a very important aspect of Master's level research for students and an essential element of research reporting. Moreover, it gives good ideas and way-out in thesis writing. DOI: http://dx.doi.org/10.3126/ttp.v13i0.11548 The Third Pole Vol. 13, 2013 Page 57-59